Адміністративні акти як засоби протидії корупції в органах внутрішніх справ - Небрат, О. О.; Nebrat, O. O.; Салманова, О. Ю.; Salmanova, O. Y.; Olena Salmanova (Журнал східноєвропейського права. – 2015. – № 21. - С. 79-85, 2015)
У статті автор досліджує адміністративні акти органів внутрішніх справ, їх сутність, ознаки та види. Розглядається проблема реалізації правових розпоряджень, які стосуються протидії корупції в органах внутрішніх справ. Узагальнено основні точки зору щодо індивідуальних адміністративних актів органів внутрішніх справ та пропозиції стосовно вдосконалення законодавства у цій сфері. Визначено, що індивідуальні акти найбільш поширені в практиці державно-управлінської діяльності, оскільки вони найбільшою мірою відповідають її виконавчому призначенню і служать найважливішим засобом оперативного вирішення поточних питань управління. Зазначено, що на підставі та на виконання законів, які визначають механізм протидії корупції, в органах внутрішніх справ приймається цілий ряд актів застосування норм адміністративного права.

The author examines the administrative acts of the bodies of internal affairs, their essence, features and types. The issue of implementation of legal regulations related to anti-corruption in the bodies of internal affairs have been highlighted. The main ideas on individual administrative acts of the bodies of internal affairs have been analyzed and proposals to improve legislation in this area have been made. It was determined that individual acts are common in practice of state-administrative activity, as they comply with its purpose and executive function. Attention has been drawn to the fact that internal affairs bodies approve a set of acts which apply the rules of administrative law in accordance with laws that provide the mechanism of anti-corruption. It has been proved that law enforcement acts have the same nature as the acts issued by other state authorities. They are individual, imperious, binding, regulating and can cause certain legal consequences. It is concluded that the act which applies the rules of administrative law is an objective expression, made by the actions of a particular agency or official on the application of these rules. The need to publish the executive regulations, which contain rules of administrative law enforcement regulations and requirements arising from the legislation on corruption has been proved.

В статье автор исследует административные акты органов внутренних дел, их сущность, признаки и виды. Рассматривается проблема реализации правовых предписаний, касающихся противодействия коррупции в органах внутренних дел. Обобщены основные точки зрения в отношении индивидуальных административных актов органов внутренних дел и предложения по совершенствованию законодательства в этой сфере. Определено, что индивидуальные акты наиболее распространены в практике государственно-управленческой деятельности, поскольку они в наибольшей степени соответствуют его исполнительному назначению и служат важнейшим средством оперативного решения текущих вопросов управления. Указано, что на основании и во исполнение законов, которые определяют механизм противодействия коррупции, в органах внутренних дел принимается целый ряд актов применения норм административного права.
Administrative Acts as an Element of the Fight against Corruption in the Bodies of Internal Affairs
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; адміністративні акти; корупція; законність; контроль; нагляд; компетенція; відповідальність; административные акты; коррупция; законность; контроль; надзор; компетенция; ответственность; administrative acts; corruption; legality; control; supervision; competence; responsibility